Evaluation of Efficacy of 1064 nm Q Switched Nd:YAG Laser Treatment in the Nevus of Ota: Seven-year Retrospective Study - Neenu Kaul; Neeti Kumari; Shiv D. S. Rawat (Journal of Dermatology and Dermatologic Surgery)
Background: Nevus of Ota is a benign skin condition characterized by dermal melanocytosis. Q switched Nd:YAG laser (QSNYL) has become the mainstay of therapy for treating this condition probably because of the minimum side effects and their noninvasive nature. Purpose: The aim of the present study was to determine the efficacy of QSNYL in the treatment of nevus of Ota in Indian skin phototypes. Methods: Patients with the clinical diagnosis of nevus of Ota who had underwent multiple treatment sessions with QSNYL at 4 weekly intervals from March 2016 to March 2023 over 6 years were enrolled in the study. Serial photographs taken before starting laser treatment and after every laser session were assessed to see the effectiveness of the treatment and graded on a scale of 0–IV. Results: A total of 36 patients were treated with QSNYL. Their age ranged from 15 to 35 years. Out of 36 patients, 12 (33%) patients showed moderate improvement, 4 (11%) patients showed marked improvement, while mild improvement (<25%) was seen in 10 (27.8%) patients. Eight (22%) patients did not show any improvement at all. Only two patients showed near total improvement of >75%. Hypopigmentation was noted in four patients. Conclusion: QSNYL is an easy-to-perform and safe treatment in cases of nevus of Ota in Indian patients with minimal side effects. On comparing our results with results in other Indian studies, we observed relatively less improvement but better tolerability of treatment in our patients.